Mejora de procesos de gestión para reducir los costos operativos en la empresa Inversiones & Contratistas Zayd S.A.C.-2018 - Cruzado Polo, Denis Perciles (2019)
The following research had the general objective of improving the management processes in the company Inversiones & Contractors Zayd SAC, to reduce operating costs, having as a research problem: How does the improvement of management processes reduce the operating costs of the company Inversiones & Contractors Zayd SAC ?, whose research hypothesis is: The improvement of management processes significantly reduces operating costs in the company Inversiones & Contractors Zayd SAC - 2018. The population was made up of 25 employees of the company, whose sample is 25 employees, the type of research is explanatory. The results obtained are: 48% of the collaborators indicate that the level of process management of the company Inversiones & Contractors Zayd S.A.C. it is bad, 32% indicate that it is fair and 20% indicate that it is good. The operating costs of the company before the improvement were S / 1,053,500.26 and after the improvement it was S / 968,002.92. We have to improve processes if it reduces operating costs by S / 85,497.34 per year. In conclusion, the results of the investigation indicated that the improvement of management processes reduces operating costs in the company Inversiones & Contractors Zayd S.A.C.-2018.